Structure of Pinus sylvestris L. populations in Bulgaria revealed by chloroplast microsatellites and terpenes analysis: Provenance tests - Naydenov, Krassimir D.; Tremblay, Francine M.; Alexandrov, Alexander; Fenton, Nicole J. (Biochemical systematics and ecology, 2005)
In the present study we investigated the genetic structure and genetic diversity of Pinus sylvestris populations in Bulgaria using chloroplast microsatellite markers and terpene analysis. We were interested in addressing the following questions: (1) can population structure in Scots pine be detected via chloroplast microsatellites markers and terpenes; (2) are there differences in population differentiation between the two analyses; and (3) how are the patterns related to geographic distances. Twelve provenances were chosen throughout the species' range in Bulgaria. Following DNA extraction, chloroplast microsatellite (cpSSR) loci were surveyed using six primer pairs. Between 4 to 8 size variants were identified at each locus. A total of 35 size variants at the six loci were identified, 11 occurring at low frequencies (<1%). They were combined in 134 different haplotypes, of which seven represent 1/3 of the genetic structure. AMOVA analysis revealed that 10.99% of the variation was found among populations, while 89.01% was expressed within populations. The cpSSR analysis divided Scots pine populations into two groups, the first represented by populations located in the south-western part of the Rhodopes and Pirin mountains, while the second group is located in the northeast of Rhodopes and Rila mountains. Terpene analysis revealed that on average, 53% of the monoterpene pool in P. sylvestris was accounted for by α-pinene (range 47–59%) followed by β-pinene (range 6–12%). The presence of two distinct groups is weekly consistent with physical distances between populations, similar significant correlation between genetic distance determined by chloroplast microsatellites analysis and chemotype distance (determined by terpenes) was observed. Our results suggest that the structural pattern of genetic diversity of cpDNA in Scots pine populations is the consequence of historical biogeographic processes.